Dollarization Dilemma : Price Stability at the Cost of External Competitiveness in Cambodia - Samreth, Sovannroeun (World Bank, Washington, DC, 2019)
Cambodia has recorded both rapid economic growth and macroeconomic stability in recent decades despite (or thanks to) high levels of dollarization. Previous studies on dollarization in Cambodia have largely focused on examining its causes and estimating seigniorage losses. As an attempt to further explore the effects of dollarization in Cambodia, this paper examines its impact on the competitiveness of the export sector. The main results, based on a vector autoregression estimation of quarterly data over 1994Q4-2016Q4, indicate that a positive US interest rate shock has a negative impact on Cambodia's trade balance with the European Union, its main trading partner, as it leads to appreciation of the US dollar. Furthermore, this shock also leads to a significant decrease in Cambodia's international reserve levels during the first two quarters following the shock. The surrendering of monetary and exchange rate independence seems to affect the competitiveness of the tradable sector negatively as well as exacerbate financial sector vulnerability to solvency and liquidity risks.